Effect of non-genetic factors on prolificacy and pre-weaning kid mortality of Khari goats in Nawalpur, Nepal - Bhattarai, Nirajan (Journal of Agriculture and Natural Resources, 2021)
Present study was carried out mainly aiming at studying the effect of non-genetic factors on prolificacy and pre-weaning kid mortality of Khari goats in Nawalpur, Nepal. The traits were recorded for 1005 does were measured and analyzed using fixed effect Least Square Mixed Model and Maximum Likelihood Computer Program (LSMMML PC-2). Results revealed that overall mean prolificacy and pre-weaning kid mortality in this study were 145 and 6.2%, respectively. According to the results, non-genetic factors such as altitude, coat color and dam’s parity were the important sources of variation with respect to pre-weaning kid mortality and prolificacy of Khari goats in this study. Thus, the results of present study suggested the scope of improvement in prolificacy and pre-weaning kid mortality through selective breeding.